2012
DOI: 10.1155/2012/576719
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Endoscopy in the Evaluation of Pediatric Obstructive Sleep Apnea

Abstract: Pediatric obstructive sleep apnea (OSA) is not always resolved or improved with adenotonsillectomy. Persistent or complex cases of pediatric OSA may be due to sites of obstruction in the airway other than the tonsils and adenoids. Identifying these areas in the past has been problematic, and therefore, therapy for OSA in children who have failed adenotonsillectomy has often been unsatisfactory. Sleep endoscopy is a technique that can enable the surgeon to determine the level of obstruction in a sleeping child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…In complex or persistent cases of OSA, sleep endoscopy is a technique that enables the exact level of obstruction in the child to be identified, thus facilitating site-specific surgical therapy 163,164. Further work to delineate the children who would benefit most from these procedures is needed, but some recent work in obese children and in children with trisomy 21 showed that lingual tonsils may contribute to residual disease and that lingual tonsillectomy may be effective in those cases 165171…”
Section: Treatmentmentioning
confidence: 99%
“…In complex or persistent cases of OSA, sleep endoscopy is a technique that enables the exact level of obstruction in the child to be identified, thus facilitating site-specific surgical therapy 163,164. Further work to delineate the children who would benefit most from these procedures is needed, but some recent work in obese children and in children with trisomy 21 showed that lingual tonsils may contribute to residual disease and that lingual tonsillectomy may be effective in those cases 165171…”
Section: Treatmentmentioning
confidence: 99%
“…The examination requires general anestesia that is usually induced with the use of anesthetic gas agents (Nitrous oxide/O2 admixture at 30/70%) and, when an adequate level of sedation is obtained, it is maintained with an intravenous infusion of propofol (100 mcg/Kg/min) and remi-fentanyl (100 ng/Kg/die) [15,16]. Some authors prefer an infusion of dexmedetomidine (1-2 mcg/Kg/hr) without a loading dose with a concurrent ketamine bolus of 1 mg/Kg that seems to induce less muscular relaxation and a more sustained respiratory effort [17]. The technique was first described in the late eighties [18,19] and subsequently validated in several independent studies [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Capasso et al have Tongue base 33.3 % (3/9) 11.1 % (1/9) Epiglottis 11.1 % (1/9) 0 % (0/9) 0 % (0/9) 0 % (0/9) BMI body mass index, AHI apnea-hypopnea index, A-P anteroposterior, n/a not available a Patients with partial or complete anterior-posterior tongue base collapse were associated with a significantly higher AHI (P = 0.016) compared to patients with no anterior-posterior tongue base collapse reported that DISE with propofol group had a significantly increased likelihood of demonstrating complete tongue base obstruction compared to DISE with dexmedetomidine group [30]. In addition, Lin et al also stated that the use of propofol may cause excessive hypotonia and muscle relaxation resulting in inaccurate airway evaluation [31]. However, Yoon et al have found that the upper airway collapse during DISE sedated with propofol and dexmedetomidine were in excellent agreement [32].…”
Section: Discussionmentioning
confidence: 99%